Portal vein thrombosis in a noncirrhotic patient after hemihepatectomy: A case report and review of literature - Zhang, Shu-Bin; Hu, Zi-Xuan; Xing, Zhong-Qiang; Li, Ang; Zhou, Xin-Bo; Liu, Jian-Hua (World journal of clinical cases, 2022)
Portal vein thrombosis (PVT) is a condition caused by hemodynamic disorders. It may be noted in the portal vein system when there is an inflammatory stimulus in the abdominal cavity. However, PVT is rarely reported after hepatectomy. At present, related guidelines and major expert opinions tend to consider vitamin K antagonists or low-molecular weight heparin (LMWH) as the standard treatment. But based on research, direct oral anticoagulants may be more effective and safe for noncirrhotic PVT and are also beneficial by reducing the recurrence rate of PVT.BACKGROUNDPortal vein thrombosis (PVT) is a condition caused by hemodynamic disorders. It may be noted in the portal vein system when there is an inflammatory stimulus in the abdominal cavity. However, PVT is rarely reported after hepatectomy. At present, related guidelines and major expert opinions tend to consider vitamin K antagonists or low-molecular weight heparin (LMWH) as the standard treatment. But based on research, direct oral anticoagulants may be more effective and safe for noncirrhotic PVT and are also beneficial by reducing the recurrence rate of PVT.A 51-year-old woman without any history of disease felt discomfort in her right upper abdomen for 20 d, with worsening for 7 d. Contrast-enhanced computed tomography (CECT) of the upper abdomen showed right liver intrahepatic cholangiocarcinoma with multiple intrahepatic metastases but not to the left liver. Therefore, she underwent right hepatic and caudate lobectomy. One week after surgery, the patient underwent a CECT scan, due to nausea, vomiting, and abdominal distension. Thrombosis in the left branch and main trunk of the portal vein and near the confluence of the splenic vein was found. After using LMWH for 22 d, CECT showed no filling defect in the portal vein system.CASE SUMMARYA 51-year-old woman without any history of disease felt discomfort in her right upper abdomen for 20 d, with worsening for 7 d. Contrast-enhanced computed tomography (CECT) of the upper abdomen showed right liver intrahepatic cholangiocarcinoma with multiple intrahepatic metastases but not to the left liver. Therefore, she underwent right hepatic and caudate lobectomy. One week after surgery, the patient underwent a CECT scan, due to nausea, vomiting, and abdominal distension. Thrombosis in the left branch and main trunk of the portal vein and near the confluence of the splenic vein was found. After using LMWH for 22 d, CECT showed no filling defect in the portal vein system.Although PVT after hepatectomy is rare, it needs to be prevented during the perioperative period.CONCLUSIONAlthough PVT after hepatectomy is rare, it needs to be prevented during the perioperative period.